The dragon in the library - Klimo, Kate; Shroades, John (New York : Random House, 2010)
Dragon Keepers Jesse and Daisy, along with their dragon, Emmy, must save their friend Professor Andersson from an evil witch, who happens to be St. George the Dragon Slayer's girlfriend
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Libraries -- Juvenile fiction; Cousins -- Juvenile fiction